2021
DOI: 10.29103/jspm.v2i1.3696
|View full text |Cite
|
Sign up to set email alerts
|

Rokok Elektrik (Vape) sebagai Gaya Hidup Perokok Masa Kini di Kota Lhokseumawe

Abstract: In all parts of the world, every human being has various kinds of habits. One of the human habits is smoking. Today, smoking itself is not something that is considered taboo by society. Cigarettes have become objects that are familiar to humans in general. This smoking habit is difficult to break. On this occasion, researchers will try to raise a theme of smoking habits that have become more modern among teenagers, namely vape as a lifestyle for today's smokers. The background of this research is the author's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…This indicates that consumers of e-cigarettes and vapes will be required to make fewer purchases of traditional cigarettes. The e-liquid may be used several times over two weeks, and when the costs of conventional and electronic cigarettes are compared overall, traditional cigarettes are significantly more expensive (Hutapea & Fasya, 2021;Zhu et al, 2014). Research by Rutter et al (2017) found that adolescents thought that if tobacco became too expensive, 44% said they would consider trying an e-cigarette or would use one more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that consumers of e-cigarettes and vapes will be required to make fewer purchases of traditional cigarettes. The e-liquid may be used several times over two weeks, and when the costs of conventional and electronic cigarettes are compared overall, traditional cigarettes are significantly more expensive (Hutapea & Fasya, 2021;Zhu et al, 2014). Research by Rutter et al (2017) found that adolescents thought that if tobacco became too expensive, 44% said they would consider trying an e-cigarette or would use one more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies conducted, the vape industry has formed a fan culture (Hutapea & Fasya, 2021) or a new subculture. In urban areas, vape communities continue to grow.…”
Section: Vape In Scot Perspectivementioning
confidence: 99%
“…In this case, some groups of people interpret vaping, which was originally a smoking cessation tool or a substitute for tobacco cigarettes to minimize the dangers of nicotine and tar, as a famous artifact. Several previous studies stated that vaping has changed or been interpreted as a lifestyle symbol (Hutapea & Fasya, 2021;Mixdam et al, 2020;Santana et al, 2018). The symbol then determines the social class of the user.…”
Section: Vape In Scot Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The Central Statistics Agency (Badan Pusat Statistik) reported that cigarettes are categorized as the main consumption of the Indonesian people and the average expenditure on cigarettes and tobacco was IDR 76,583 per capita per month in March 2021 (Jayani 2021). This causes Indonesia to be the country with the third largest number of smokers in the world (Fikriyah & Febrijanto 2012;Hutapea & Fasya 2021).…”
Section: Introductionmentioning
confidence: 99%